Professional Competency of Pre-Service English Teachers and ICT during Covid-19 Pandemic - Rizkiani, Siska (LPPM Universitas Advent Indonesia, 2021)
Professional competence of pre-service English teachers needs to be done in an effort to find effective ways in improving their teaching performance, which requires the proper implementation of ICT in online learning. This study aims at investigating the level of professional competence of pre-service English teachers in vocational high schools in applying ICT in learning during the Covid-19 pandemic. It adopts a quantitative approach. It is a type of survey research because it only describes the condition of the research respondents without any treatment being carried out. The respondents of this study were 83 English pre-service teachers of the IKIP Siliwangi who were undergoing teaching training subjects at various vocational schools. This research was conducted by distributing questionnaires and conducting interviews. The results showed that the professional competence of pre-service English teachers in implementing ICT is at a very good level, which means that pre-service teachers have not performed excellent competence. This can be proven from the tendency of the three assessors (in-service teachers, supervisors, and students) to state that almost all aspects of pre-service teachers are at a very good competency level. These aspects are teaching and learning activities, teaching administration management, assignments, implementation of evaluation, and the right tools. Only on the delivery of information aspect, pre-service teachers get a good competency level.